Estimating Reliability and Ranking of Wind Turbine Plant under Fuzzy Environment Through Generalized Trapezoidal Fuzzy Numbers (GTFNs) - Amit Kumar; Pramod Yelam (International Journal of Mathematical, Engineering and Management Sciences)
Reliability and ranking estimation of complex systems such as Wind Turbine plant (WTP) is essential for their efficient operation and vulnerability to the operational issues and conditions. Thus, this paper addresses the importance of the reliability assessment of a wind turbine plant incorporating both the routine as well as preventive maintenance strategies using Fuzzy logic. Wind turbines, which are used for the power generation through renewable sources of energy, require effective reliability analysis for the optimal level of performance. For this, generalized trapezoidal fuzzy numbers (GTFNs) are introduced with certain level of confidence. Lambda-Tau methodology together with GTFNs and associated mathematical operations have been employed for calculating the different performance measures e.g. Reliability, Availability, Maintainability, Mean Time to Failure, Mean Time to Repair, Mean Time Between Failure, Expected Number of Failure (ENOF) of the wind turbine plant. Authors also performed ranking analysis for the components of WTP to determine the key components of the same. The outcome of the study can be considered as a valuable reference to the maintenance team to plan strategy in a better way. Based on the results, it can be concluded that this methodology is highly effective for the performance analysis of WTP system. Additionally, the authors have outlined the future scope of the research work at the end of the conclusion section.